Colorectal liver metastases with a disrupted circadian rhythm phase shift the peripheral clock in liver and kidney. Issue 5 (4th August 2014) - Huisman, Sander A.; Oklejewicz, Malgorzata; Ahmadi, Ali R.; Tamanini, Filippo; Ijzermans, Jan N.M.; van der Horst, Gijsbertus T.J.; de Bruin, Ron W.F.
<x xml:space="preserve">Abstract</x> Circadian clock genes regulate 10–15% of the transcriptome, and might function as tumor suppressor genes. Relatively little is known about the circadian clock in tumors and its effect on surrounding healthy tissues. Therefore, we compared the 24‐hr expression levels of key circadian clock genes in liver and kidney of healthy control mice with those of mice bearing C26 colorectal tumor metastases in the liver. Metastases were induced by injection of C26 colorectal carcinoma cells into the spleen. Subsequently, tumor, liver and kidney tissue was collected around the clock to compare circadian rhythmicity. Expression levels of five clock genes (Rev‐Erbα, Per1, Per2, Bmal1 and Cry1) and three clock‐controlled genes (CCGs; Dbp, p21 and Wee1) were determined by qRT‐PCR. Liver and kidney tissue of healthy control mice showed normal 24‐hr oscillations of all clock genes and CCGs, consistent with normal circadian rhythmicity. In colorectal liver metastases, however, 24‐hr oscillations were completely absent for all clock genes and CCGs except Cry1. Liver and kidney tissue of tumor‐bearing mice showed a shift in clock periodicity relative to control mice. In the liver we observed a phase advance, whereas in the kidney the phase was delayed. These data show that hepatic metastases of C26 colon carcinoma with a disrupted circadian rhythm phase shift liver and kidney tissue clocks, which strongly suggests a systemic effect on peripheral clocks. The possibility that tumors may modify peripheral clocks to escape from ordinary circadian rhythms and in this way contribute to fatigue and sleep disorders in cancer patients is discussed.